Impact of nutrients and water level changes on submerged macrophytes along a temperature gradient: A pan‐European mesocosm experiment - Zeynep Ersoy; Ulrike Scharfenberger; Didier L. Baho; Tuba Bucak; Tõnu Feldmann; Josef Hejzlar; Eti E. Levi; Aldoushy Mahdy; Tiina Nõges; Eva Papastergiadou; Konstantinos Stefanidis; Michal Šorf; et al. (Global Change Biology, 2020)
Submerged macrophytes are of key importance for the structure and functioning of shallow lakes and can be decisive for maintaining them in a clear water state. The ongoing climate change affects the macrophytes through changes in temperature and precipitation, causing variations in nutrient load, water level and light availability. To investigate how these factors jointly determine macrophyte dominance and growth, we conducted a highly standardized pan‐European experiment involving the installation of mesocosms in lakes. The experimental design consisted of mesotrophic and eutrophic nutrient conditions at 1 m (shallow) and 2 m (deep) depth along a latitudinal temperature gradient with average water temperatures ranging from 14.9 to 23.9°C (Sweden to Greece) and a natural drop in water levels in the warmest countries (Greece and Turkey). We determined percent plant volume inhabited (PVI) of submerged macrophytes on a monthly basis for 5 months and dry weight at the end of the experiment. Over the temperature gradient, PVI was highest in the shallow mesotrophic mesocosms followed by intermediate levels in the shallow eutrophic and deep mesotrophic mesocosms, and lowest levels in the deep eutrophic mesocosms. We identified three pathways along which water temperature likely affected PVI, exhibiting (a) a direct positive effect if light was not limiting; (b) an indirect positive effect due to an evaporation‐driven water level reduction, causing a nonlinear increase in mean available light; and (c) an indirect negative effect through algal growth and, thus, high light attenuation under eutrophic conditions. We conclude that high temperatures combined with a temperature‐mediated water level decrease can counterbalance the negative effects of eutrophic conditions on macrophytes by enhancing the light availability. While a water level reduction can promote macrophyte dominance, an extreme reduction will likely decrease macrophyte biomass and, consequently, their capacity to function as a carbon store and food source.

Bryophyte communities of Mediterranean Europe: a first approach to model their potential distribution in highly seasonal rivers - C. Vieira; F. C. Aguiar; A. P. Portela; J. Monteiro; P. J. Raven; N. T. H. Holmes; J. Cambra; N. Flor-Arnau; C. Chauvin; S. Loriot; T. Feret; G. Dörflinger; et al. (Hydrobiologia, 2018)

Erratum to: Influence of hydrophyte abundance on the spatial distribution of zooplankton in selected lakes in Greece - K. Stefanidis; E. Papastergiadou (Hydrobiologia, 2017)

Exploring biodiversity in riparian corridors of a Mediterranean island: Plant communities and environmental parameters in Cyprus rivers - E. Papastergiadou; K. Stefanidis; G. Dorflinger; E. Giannouris; K. Kostara; P. Manolaki (Plant Biosystems, 2016)

New Mediterranean Marine biodiversity records (June 2013) - I. SIOKOU; A.S. ATES; D. AYAS; J. BEN SOUISSI; T. CHATTERJEE; M. DIMIZA; H. DURGHAM; K. DOGRAMMATZI; D. ERGUDEN; V. GERAKARIS; M. GREGO; Y. ISSARIS; et al. (Mediterranean Marine Science, 2013)
This paper concerns records of species that have extended their distribution in the Mediterranean Sea. The finding of the rare brackish angiosperm Althenia filiformis in the island of Cyprus is interesting since its insertion in the Red Data Book of the Flora of Cyprus is suggested. The following species enriched the flora or fauna lists of the relevant countries: the red alga Sebdenia dichotoma (Greece), the hydrachnid mite Pontarachna adriatica (Slovenia), and the thalassinid Gebiacantha talismani (Turkey). Several alien species were recorded in new Mediterranean localities. The record of the burrowing goby Trypauchen vagina in the North Levantine Sea (Turkish coast), suggests the start of spreading of this Lessepsian immigrant in the Mediterranean Sea. The findings of the following species indicate the extension of their occurrence in the Mediterranean Sea: the foraminifer Amphistegina lobifera (island of Zakynthos, Greece), the medusa Cassiopea andromeda (Syria), the copepod Centropages furcatus (Aegean Sea), the decapod shrimp Melicertus hathor (island of Kastellorizo, Greece), the crab Menoethius monoceros (Gulf of Tunis), the barnacles Balanus trigonus, Megabalanus tintinnabulum, Megabalanus coccopoma and the bivalves Chama asperella, Cucurbitula cymbium (Saronikos Gulf, Greece).

Responses of aquatic macrophyte assemblages to nutrient enrichment in a lowland river basin of western Greece - P. Manolaki; E. Papastergiadou (Plant Biosystems, 2012)

Influence of hydrophyte abundance on the spatial distribution of zooplankton in selected lakes in Greece - K. Stefanidis; E. Papastergiadou (Hydrobiologia, 2010)

Effects of Anthropogenic Influences on the Trophic State, Land Uses and Aquatic Vegetation in a Shallow Mediterranean Lake: Implications for Restoration - E. Papastergiadou; I. Kagalou; K. Stefanidis; A. Retalis; I. Leonardos (Water Resources Management, 2010)

Environmental Monitoring of Spatio-temporal Changes Using Remote Sensing and GIS in a Mediterranean Wetland of Northern Greece - E. S. Papastergiadou; A. Retalis; A. Apostolakis; Th. Georgiadis (Water Resources Management, 2008)

Land use changes and associated environmental impacts on the Mediterranean shallow Lake Stymfalia, Greece - E. S. Papastergiadou; A. Retalis; P. Kalliris; Th. Georgiadis (Hydrobiologia, 2007)

Evaluation of the trophic state of Lake Pamvotis Greece, a shallow urban lake - I. Kagalou; E. Papastergiadou; G. Tsimarakis; D. Petridis (Hydrobiologia, 2003)